LOYALITAS MEREK MELALUI PENGALAMAN MEREK DAN NILAI PELANGGAN SMARTPHONE XIAOMI - Cahyani Pratisti (Politeknik Bisnis Indonesia, 2022)
The competition between smartphone manufacturers is getting tougher along with the increasing demand for smartphones. Brand loyalty is important for companies because it can predict future purchases. This study aims to determine the effect of brand experience on the loyalty of the Xiaomi smartphone, to determine the effect of customer value on the Xiaomi smartphone brand loyalty, and to determine the effect of brand experience and customer value on Xiaomi smartphone brand loyalty. This causality quantitative study used a survey method with a close questionnaire instrument distributed online to 300 respondent. Through multiple linear regression, t test and F test analysis, it was found that brand experience and customer value both partially and simultaneously affecedt Xiaomi smartphone brand loyalty. This proves that manufacturers should pay more attention to brand experience and customer value to strengthen the brand equity and increase in sales.